A Mixed Blessing: Impact of Covid-19 on Authors and Libraries in Zambia - Pethias Siame; Jive Lubbungu; Christian Ehiobuche (ARRUS Journal of Social Sciences and Humanities, 2023)
The study examines the impact of Covid-19 on authors and libraries in Zambia. Data were collected for three weeks through in-depth interviews via WhatsApp platform and phone calls with the participants. Being a qualitative study, 15 participants were randomly selected from a sampling framework of 157 respondents. Ten participants were authors while five were librarians. The phenomenological approach was found apposite for this study because it involved collecting, describing, and examining participants' individual lived experiences about a particular phenomenon, in this case, the Covid-19 pandemic impact. The data were analysed thematically according to the general steps for analysing phenomenological data as presented by LoBiondo and Hubee (1988). The study shows that the impact of Covid-19 on authors and libraries is something of a double-edged sword. While on the downside, it has reduced book sales, increased the cost of publishing, and threatened job security and access to resources, on the upside it has challenged authors and libraries to think outside the box. Authors are challenged to maximise digital resources while libraries should invest in digital resources and virtual libraries. The study concludes that the Covid-19 pandemic has impacted negatively as well as positively on the book industry in Zambia.